Hubungan Antara Perilaku Agresif Dengan Kenakalan Remaja di Kelurahan Kwala Begumit Binjai - Sari, Devi Wiana; Aziz, Azhar (Universitas Medan Area, 2025)
Adolescence is a developmental phase that is prone to deviant behavior, one of which is juvenile delinquency. This phenomenon not only harms individuals, but also has an impact on social security. One of the factors believed to be closely related to juvenile delinquency is aggressive behavior, both verbal and physical. This study aims to determine the relationship between aggressive behavior and juvenile delinquency in Kwala Begumit Binjai Village. The research uses a quantitative approach with a correlational design. The study population was 247 adolescents, with 88 people as samples through purposive sampling techniques based on criteria of having committed delinquency in the past year. The instrument is in the form of the Likert scale which is compiled based on the aspects of Hurlock (1980) and Berkowitz (2005). Data analysis was carried out with Pearson's Product Moment correlation after going through validity, reliability, normality, and linearity tests. The results showed a very strong positive relationship between aggressive behavior and juvenile delinquency (r = 0.983; p 0.05), with a contribution of 93.1%. This proves that the higher the aggressive behavior, the higher the level of delinquency. Therefore, aggressive control through parenting, peer influence, and social intervention is needed to prevent juvenile delinquency.